A new pleiotropic effect of statins in elderly: modulation of telomerase activity. Issue 9 (7th June 2013) - Boccardi, Virginia; Barbieri, Michelangela; Rizzo, Maria Rosaria; Marfella, Raffaele; Esposito, Antonietta; Marano, Luigi; Paolisso, Giuseppe
Abstract : Recent evidence suggests a link between statins and telomere biology. Whether statin treatment may modulate telomerase activity and affect telomere erosion rate is unknown. We aimed at investigating the potential impact of statin therapy on peripheral blood mononuclear cells telomerase activity, its implication on LTL variability, and its association with telomere shortening rates along with aging. The cross‐sectional study was conducted in 230 subjects (age range: 30‐86 y) stratified according to statins treatment. LTL was measured by quantitative polymerase chain reaction and telomerase activity by a PCR‐ELISA protocol. Subjects on statin treatment showed higher telomerase activity ( P <0.0001) and longer LTL ( P = 0.028) levels compared to the nonstatin group. Statin therapy was associated with higher telomerase activity independently of multiple covariates, including age, gender, smoking habits, lipid, systemic inflammation, glucose, and blood pressure levels ( P =0.019). Indeed, subjects on statin treatment showed significant lower telomere erosion along with aging. Every 1 y increment in age, LTL decreases by 0.058 Kb in no statin and 0.033 Kb in statin groups, respectively, as well as the major difference in telomere attrition between groups was found after the age of 65 yr ( P <0.0001). In summary, statins, modulating telomerase activity, affect telomere erosion along with aging.—Boccardi, V., Barbieri, M., Rizzo, M. R., Marfella, R., Esposito, A., Marano, L., Paolisso, G., A new pleiotropic effect of statins in elderly: modulation of telomerase activity FASEB J. 27, 3879–3885 (2013). www.fasebj.org